'Fundermediaries' in Nairobi, Kenya: Development Partnerships in the Aid Chain. Issue 2 (3rd March 2023) - Woensdregt, Lise; Nencel, Lorraine
ABSTRACT: By representing the voice of communities, community‐based organizations (CBOs) are increasingly joining development partnerships. This article explores the inherently contradictory relationship between 'voice raising' and the politics of listening. While academia has mostly focused on the inclusion of CBOs, few studies have approached this subject from the perspective of the listening practices of 'fundermediaries' (a portmanteau term combining 'funder' and 'intermediary'). This ethnographic research on a CBO led by male sex workers in Nairobi, Kenya, illustrates that the listening ability of fundermediaries hinges on their position in the aid chain, and specifically on the dynamics of their own accountability. The analysis distinguishes between two partnership types. The first uses a pragmatic approach, which ultimately limits the channels for CBOs to be included and heard, resulting in them having to 'make noise' to ensure they are heard. The second creates more possibilities to listen, engages in constructive dialogues with partner CBOs, and includes the ideas and expertise of CBOs in development strategies; hence, CBOs feel heard and are positive about these partnerships. Improved listening practices facilitate opportunities to reconfigure the position of the different actors in development partnerships and can benefit both the positions of CBOs in the aid chain and the programmatic outcomes of fundermediaries.